Nitrate Removal from Aqueous Solution by Hexadecyltrimethylammonium Bromide-Modified Clinoptilolite - Dikmen, S.; Yorukogullari, E. (Asian Journal of Chemistry, 2011)
In the first stage of study, detailed characterization studies were performed on clinoptilolite-rich tuff mined from the Gördes/Manisa region (Turkey). The physical and chemical properties were determined using instrumental analysis techniques, including XRD, XRF, SEM, DTG-DTA and specific surface area. In the second stage, modification of clinoptilolite-rich tuff surface with hexadecyltrimethyl-ammonium bromide (HDTMA) to improve the adsorption efficiency of nitrate was performed using a batch equilibration method. The surface modification of clinoptilolite with a surfactant was examined using the FT-IR spectroscopic technique and equilibrium data. The Langmuir and Freundlich adsorption models were applied to describe the equilibrium isotherms and the isotherm constants were also determined. The equilibrium data are fitted to the Freundlich adsorption isotherm. The kinetic models were used to describe the kinetic data and the rate constants were evaluated. The experimental data fitted well the pseudosecond- order kinetic model and also followed the intraparticle diffusion model up to 1 h.